Analisis penentuan tarif kamar rawat inap dengan metode cost plus pricing di Rumah Sakit Umum Daerah (RSUD) ODSK Provinsi Sulawesi Utara - Tumuju, Militia Pratiwi; Weku, Pricilia (Yayasan Widyantara Nawasena Raharja, 2025)
Hospitals are service-oriented institutions that provide essential healthcare services to the community. The determination of hospital room rates is a critical management decision that must be carefully calculated. This study aims to analyze the determination of inpatient room rates at the ODSK Regional General Hospital of North Sulawesi Province using the cost plus pricing method. The research employs a qualitative approach with descriptive analysis. The results indicate that room rates calculated using the cost plus pricing method are lower than the rates set by the hospital. Specifically, the VVIP room rate is IDR 1,148,981.00, with a difference of IDR 91,019.00 (7.34%). The VIP room rate shows a difference of IDR 83,608.00 (8.36%), Class I differs by IDR 88,205.00 (18.38%), Class II by IDR 72,612.00 (21.36%), and Class III by IDR 72,364.00 (40.20%). These discrepancies arise due to differences in the hospital's internal pricing determination and the calculations based on the cost plus pricing method.